ANALISIS PERGERAKAN BINTIK MATAHARI DI DAERAH AKTIF NOAA 0375 - Clara Y.Yatini; E.Sungging Mumpuni (Lembaga Penerbangan dan Antariksa Nasional, 2006)
The observation of flaring sunspots group (active region) has been conducted to obtain the characteristic of spot's motion. In active region NOAA 0375 the motion is divided in two periods, 3-8 June 2005, when the group was growing, and 10-12 June 2003 when it was decaying. By comparing the movement plots, we see that the strong flares were most produced when the active region was in the decaying phase.